2020
DOI: 10.1111/cxo.12927
|View full text |Cite
|
Sign up to set email alerts
|

Impact of classifying keratoconus location based on keratometry or pachymetry on progression parameters

Abstract: Background This study sought to assess the impact of classifying keratoconus location based on thinnest pachymetry or maximum keratometry (Kmax) on progression parameters after corneal crosslinking (CXL). Methods In this observational study, patients were followed up at one, three, six and 12 months after CXL. All patients underwent visual acuity, Scheimpflug tomography and slitlamp assessment at all follow‐ups. Keratoconus was classified as central, paracentral and peripheral based on X and Y co‐ordinates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
2
10
0
1
Order By: Relevance
“…Sağlık et al . [ 21 ] showed significant regression in parameter A 1 year after CXL, which coincides with the results of Bardan,[ 16 ] but differs from the results of the current study. Bardan et al .…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Sağlık et al . [ 21 ] showed significant regression in parameter A 1 year after CXL, which coincides with the results of Bardan,[ 16 ] but differs from the results of the current study. Bardan et al .…”
Section: Discussionsupporting
confidence: 69%
“…Bardan et al . [ 16 ] did not report any significant changes in parameter B over time. The results of our study differ since this variable showed a significant increase 1 year postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Em relação à classificação dos pacientes quanto à gravidade da doença, o Consenso Global de Ceratocone e Doenças Ectásicas de 2015 (2) colocou esta questão em pauta e concluiu que não haveria um sistema de classificação clínica adequado para a doença e, de fato, a sua classificação sofre bastante variabilidade entre os estudos. (9,28,29) Este trabalho optou por acessar a gravidade dos casos estudados a partir do critério proposto pelo estudo CLEK, (10) que utilizou um dado ceratométrico, especificamente o Ks (ceratometria mais curva -steep keratometry), para classificar os casos em leves, moderados e graves. Os resultados mostraram uma tendência considerável em direção ao encontro de casos considerados graves, 157 (58,80%), propensão esta também encontrada e já esperada pelo estudo CLEK (10) ao se optar pelo Ks como parâmetro.…”
Section: Discussionunclassified